Atopic dermatitis epidemiology and unmet need in the United Kingdom - Cork, M; Danby, S; Ogg, G (Taylor and Francis, 2019)
Atopic dermatitis (AD), also known as atopic eczema, is a chronic inflammatory skin condition associated with a significant health-related and socioeconomic burden, and is characterized by intense itch, disruption of the skin barrier, and upregulation of type 2-mediated immune responses. The United Kingdom (UK) has a high prevalence of AD, affecting 11-20% of children and 5-10% of adults. Approximately 2% of all cases of childhood AD in the UK are severe. Despite this, most AD treatments are performed at home, with little contact with healthcare providers or services. Here, we discuss the course of AD, treatment practices, and unmet need in the UK. Although the underlying etiology of the disease is still emerging, AD is currently attributed to skin barrier dysfunction and altered inflammatory responses. Management of AD focuses on avoiding triggers, improving skin hydration, managing exacerbating factors, and reducing inflammation through topical and systemic immunosuppressants. However, there is a significant unmet need to improve the overall management of AD and help patients gain control of their disease through safe and effective treatments. Approaches that target individual inflammatory pathways (e.g. dupilumab, anti-interleukin (IL)-4 receptor α) are emerging and likely to provide further therapeutic opportunities for patient benefit.